The state’s role in the economy after a crisis the rationale behind it and recommendations - Götz, Marta (Rocznik Integracji Europejskiej, 2015)
This paper showcases a review of recent approaches towards the state role in the post-crisis economy. The background for the analysis is the support and austerity paradox. A state is supposed to stabilise the economy, stimulate growth and prevent abuses by better supervision, and at the same time to reduce the burden on society by slashing debt. A survey of the selected literature shows that the financial turbulence and recent economic downturn call for more state presence in market processes. There is a rationale behind such interventions, although, given the risks involved, a balanced and prudent approach is required. Recommendations in this respect have been formulated.